On the non-finality of physical death in classical Confucianism - Rosemont, Jr., Henry (Acta Orientalia Vilnensia, 2007)
There is probably no idea more difficult to contemplate clearly than death and dying, especially one’s own. How we think about death, however, will surely be influenced by what we think about life and living in general, and more specifically how we define ourselves as human beings. The early Confucians viewed persons very differently than contemporary Western thinkers and developed a ritual orientation grounded in the family that had both ethical and religious (but not transcendental) dimensions, in which the death of the body was not seen as abrupt and final, but rather as a stage that began before our embodiment, and will continue long after its dissolution.
Keywords: -